A comparison of different rinsing methods upon selective dissolution of iron (oxy)hydroxides in soils/sediments (Rudarsko-geološko-naftni zbornik, 2017)
Iron (oxy)hydroxides play an important role in a variety of disciplines, among others, environmental and exploration geochemistry, mineralogy, geology and soil science. In selective leaching procedures, either for the removal of (oxy)hydroxide prior to clay minerals analysis or for the determination of metals in reducible soil/sediment fractions, it is very important to preserve the entire undissolved residue. Therefore, the objectives of the study were: (1) to fi nd the most effective reagent rinsing method which follow the dissolution of (oxy)hydroxides; and (2) to test if the content of Fe (oxi)hydroxides could be determined gravimetrically. The following reagent rinsing methods were tested: (1) centrifugation, (2) filtration, (3) dialysis. The analysis was conducted on the sample of red soil with 5.12% Fe2O3. The time needed for rinsing increased in this order: centrifugation < fi ltration < dialysis. The amount of gravimetrically determined dissolved reducible fraction upon rinsing varies signifi cantly depending on the methods and it is remarkably higher than theamount of Fe2O3 calculated from iron content determined by atomic absorption in leachate. The most effective reagent rinsing method which follows the dissolution of (oxy)hydroxides using dithionite-citrate-bicarbonate is dialysis. No loss of sample is the advantage of this method, but its disadvantage is time needed for its completion. Centrifugation is relatively rapid, but can lead to loss of the smaller particles. In this case the loss was unacceptably great. Filtration using filter paper is more time consuming than centrifugation and it showed the worst results. The conclusions are that: (1) the content of Fe (oxi)hydroxides cannot be determined gravimetrically upon selective leaching; (2) rinsing of reagents after Fe (oxi)hydroxide removal prior to clay mineral analysis should be carefully selected and performed; (3) centrifugation, accepted rinsing method in all sequential extraction sequences, can cause misleading results.